Chlorhexidine–Alcohol Compared with Povidone–Iodine Preoperative Skin Antisepsis for Cesarean Delivery: A Systematic Review and Meta-Analysis - Tolcher, Mary Catherine; Whitham, Megan D.; El-Nashar, Sherif A.; Clark, Steven L. (American Journal of Perinatology, 2019)
Objective To compare chlorhexidine–alcohol with povidone–iodine solutions for skin antisepsis prior to cesarean delivery for the prevention of surgical site infection.Study Design Electronic databases MEDLINE, Embase, Scopus, and Clinicaltrials.gov were searched from inception to August 2017. Eligible studies included randomized controlled trials comparing chlorhexidine–alcohol with povidone–iodine skin preparation solutions for women undergoing cesarean delivery. The primary outcome was surgical site infection including superficial or deep wound infection. Meta-analysis was performed, and risk ratios (RRs) with 95% confidence interval (CI) were calculated using the Mantel–Haenszel random effects model. Statistical heterogeneity was assessed using Higgin's I2.Results Of 61 abstracts identified in the primary search, four studies (3,059 women) met the eligibility criteria. The risk of surgical site infection was significantly reduced with chlorhexidine–alcohol (RR: 0.72; 95% CI: 0.52–0.98). No heterogeneity across studies was observed with I2 = 0%. Subgroup analysis of superficial infection only or deep infection only showed no statistically significant difference (RR: 0.76, 95% CI: 0.54–1.08; and RR: 0.50, 95% CI: 0.23–1.10, respectively).Conclusion Preoperative skin cleansing prior to cesarean delivery with chlorhexidine–alcohol reduces surgical site infection as compared with povidone–iodine solutions.
Keywords: cesarean delivery; surgical site infection; skin antisepsis; chlorhexidine